Efforts to Improve Cognitive Learning Outcomes of Grade V Students of SDN Socah 2 through the Discovery Learning Model in Social Science Subjects. - Muhammad Nabil Azim Bin Adam; Muhammad Haykhal Priambudhi; Muaweroh; Meilina Nuril Maulida; Agung Setyawan (Sekolah Tinggi Agama Islam Nurul Islam Mojokerto, 2026)
This study aims to improve the cognitive learning outcomes of fifth-grade students in Science and Social Studies (IPAS) through the application of the Discovery Learning model at SDN Socah 2. The research was motivated by low initial student learning outcomes, where only 22.22% of students achieved the Minimum Mastery Criteria (KKM), with a class average score of 64.6. To address this issue, a Classroom Action Research (CAR) framework with a quantitative approach was employed across two cycles. Each cycle encompassed four core stages: planning, acting, observing, and reflecting. The study subjects comprised 27 fifth-grade students (11 boys and 16 girls). Data were systematically collected using diagnostic tests, learning achievement tests, observation sheets, and archival records, then analyzed descriptively by calculating mean scores and learning mastery percentages. The findings demonstrate a significant and progressive enhancement in the students' cognitive performance. In the pre-cycle phase, the average score was 64.6 with 22.22% mastery (6 students). Following the intervention in Cycle I, the average score increased to 74.6, with mastery reaching 55.6% (15 students). In Cycle II, instructional delivery was further optimized using the Jigsaw method—a Deep Learning approach—and visual poster media. Consequently, the average score peaked at 94.81, achieving a 100% mastery rate (27 students). This remarkable improvement is attributed to students' active engagement in discovering concepts through observation, data collection, information processing, verification, and drawing conclusions. Ultimately, the Discovery Learning model proves highly effective in elevating cognitive learning outcomes in elementary IPAS education.